The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2166/nh.2020.070
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of four SUDS scenarios on combined sewer overflows in Oslo, Norway: evaluating the low-impact development module of the Mike Urban model

Abstract: Abstract Paved surfaces, increased precipitation intensities in addition to limited capacity in the sewer systems, cause a higher risk of combined sewer overflows (CSOs). Sustainable drainage systems (SUDS) offer an alternative approach to mitigate CSO by managing the stormwater locally. Seven SUDS scenarios, developed based on the concept of effective impervious area reduction, have been implemented in the Grefsen catchment using the Mike Urban model. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Simulated outflows from the two models were used to derive FDCs. The derivation of FDCs was similar to the study of Hernes et al (2020). Firstly, outflow values were ranked from highest to lowest.…”
Section: Derivation Of Fdcsmentioning
confidence: 79%
See 1 more Smart Citation
“…Simulated outflows from the two models were used to derive FDCs. The derivation of FDCs was similar to the study of Hernes et al (2020). Firstly, outflow values were ranked from highest to lowest.…”
Section: Derivation Of Fdcsmentioning
confidence: 79%
“…They applied FDCs to evaluate different scenarios of SUD implementation in a catchment. Similarly, Hernes et al (2020) applied FDCs to investigate the performance of different SUD scenarios, and they concluded the suitability of FDC as a practical measure to evaluate the hydrological performance of SUDs. Using the FDC to evaluate the performance of PP was found to be limited to few studies in the literature (Fassman & Blackbourn 2010;Brown et al 2012;Winston et al 2018), and no study was found to apply the FDC for LPP systems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Norway, sewers comprising of CSSs and stormwater drains account for 35,900 km and 15,700 km, respectively, of the entire sewer system [2]. Rapid urbanization combined with increased precipitation due to climate change and low investments in the rehabilitation of aging CSSs have resulted in the increased incidence of combined sewer overflows (CSOs) in Norway [3][4][5]. A study by Nilsen et al [5] revealed a significant relationship between the volume of CSOs in the sewer network in Oslo and flood events.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient sewage network management depends not only on accurate information on the momentary sewer flows but also the future expected flows, which enables to predict and avert emergencies [9,10]. In addition, the possibility of predicting the hydraulic load of WWTP during extreme rainfalls enables to devise the algorithms for optimization of the treatment process [11].…”
Section: Introductionmentioning
confidence: 99%